Views and news from the 8th Journal of Private International Law Conference 2019 in Munich - WELLER, Matthias (Institutional Knowledge at Singapore Management University, 2019)
From 12 to 14 September 2019, the Journal of Private International Law held its 8th Conference at the University of Munich, perfectly hosted and organized by our Munich-based colleague Anatol Dutta. Nearly 150 colleagues gathered from all over the world, amongst them many of the Conflictoflaws.net editors.